Exploring the Impact of a Voice-Based AI Chatbot (Pi) on Algerian Tertiary EFL Students’ Speaking Fluency and Self-efficacy The Case of Master One and Third Year Undergraduate EFL Students at Mohamed-Cherif Messadia University, Souk Ahras - BOUKEHILI Fatma Zohra (My University, 2024)
Abstract This study explored the impact of a voice-based AI chatbot (Pi) on the speaking fluency and self-efficacy of Algerian tertiary EFL students. It aimed to create an environment that encouraged EFL learners to comfortably engage with the voice bot Pi for speaking practice. The study utilized an exploratory correlational mixed-methods approach, combining qualitative and quantitative data collection and analysis to address the research questions, achieve the research goals, and evaluate the hypotheses. Teacher interviews were conducted with four EFL teachers from Mohamed-Cherif Messaadia University to understand their perspectives on integrating AI tools as innovative ELT/L resources. A one-group pre-test-post-test quasi-experimental design was employed to assess the effect of Pi on students’ fluency and self-efficacy. The experiment consisted of 9 sessions with 13 students enrolled in the Department of English. The process began with a pre-test and pre-intervention self-efficacy questionnaire, followed by seven intervention sessions involving interaction with Pi, during which students’ behaviors were monitored through semi-structured observation. The experiment concluded with a post-test and post-intervention self-efficacy questionnaire, along with participant reflective commentaries. Findings from EFL teachers' interviews showed a positive attitude towards AI integration in the classroom, with most teachers acknowledging potential advantages and expressing enthusiasm for incorporating such tools into their teaching methods. Moreover, results revealed that the voice-based AI chatbot Pi positively influenced EFL students’ speaking fluency and self-efficacy. Post-test scores and self-efficacy questionnaire responses significantly increased after using Pi, indicating a profound effect on speaking skills. ------------------------- ملخص تستكشف هذه الدراسة تأثير روبوت الدردشة الصوتي القائم على الذكاء الاصطناعي المسمى “Pi” على طلاقة الكلام والكفاءة الذاتية لطلاب اللغة الإنجليزية كلغة أجنبية في الجزائر على المستوى الجامعي. تهدف إلى خلق بيئة تشجع متعلمي اللغة الإنجليزية كلغة أجنبية على التفاعل بشكل مريح مع الروبوت الصوتي Pi لممارسة التحدث. لمعالجة أسئلة البحث، وتحقيق أهداف البحث، وتقييم الفرضيات، استخدمت هذه الدراسة منهجية مختلطة استكشافية ترابطية، تجمع بين جمع البيانات النوعية والكمية وتحليلها. تم إجراء مقابلات مع أربعة مدرسين للغة الإنجليزية كلغة أجنبية من جامعة محمد الشريف مساعدية، لفهم وجهات نظرهم حول دمج أدوات الذكاء الاصطناعي كمصادر مبتكرة لتعليم وتعلم اللغة الإنجليزية. تم استخدام تصميم شبه تجريبي ذو مجموعة واحدة مع اختبار قبلي وبعدي لتقييم تأثير Pi على طلاقة الطلاب والكفاءة الذاتية. تألفت التجربة من 9 جلسات مع 13 طالبًا مسجلين في قسم اللغة الإنجليزية. بدأ العملية باختبار قبلي واستبيان كفاءة ذاتية قبل التدخل، تلاه سبع جلسات تدخل تضمنت تفاعلًا مع Pi، حيث تم مراقبة سلوكيات الطلاب من خلال ملاحظة شبه منظمة. اختتمت التجربة باختبار بعدي واستبيان كفاءة ذاتية بعد التدخل، إلى جانب تعليقات انعكاسية من المشاركين .أظهرت نتائج مقابلات المعلمين موقفًا إيجابيًا تجاه دمج الذكاء الاصطناعي في الفصول الدراسية، مع اعتراف معظم المعلمين بالمزايا المحتملة والتعبير عن حماسهم لإدراج مثل هذه الأدوات في طرق التدريس الخاصة بهم. علاوة على ذلك، كشفت النتائج أن روبوت الدردشة الصوتي القائم على الذكاء الاصطناعي Pi أثر بشكل إيجابي على طلاقة الكلام والكفاءة الذاتية للطلاب. زادت درجات الاختبارات البعدية واستجابات استبيان الكفاءة الذاتية بشكل كبير بعد استخدام Pi، مما يشير إلى تأثير عميق على مهارات التحدث. ----------------------- Résumé Cette étude explore l'impact d'un chatbot vocal basé sur l'IA "Pi" sur la fluidité de la parole et l'auto-efficacité des étudiants algériens en anglais langue étrangère au niveau tertiaire. Elle vise à créer un environnement qui encourage les apprenants d'anglais à s'engager confortablement avec le chatbot vocal Pi pour la pratique orale. Pour aborder les questions de recherche, atteindre les objectifs de recherche et évaluer les hypothèses, cette étude a utilisé une approche mixte exploratoire corrélationnelle, combinant la collecte et l'analyse de données qualitatives et quantitatives.Des entretiens avec des enseignants ont été menés avec quatre enseignants d'anglais l'Université Mohamed-Cherif Messaadia, pour comprendre leurs perspectives sur l'intégration des outils d'IA comme ressources innovantes dans l’enseignement / apprentissage du langue anglais. Un plan quasi-expérimental à groupe unique avec pré-test et post-test a été utilisé pour évaluer l'effet de Pi sur la fluidité et l'auto-efficacité des étudiants. L'expérience consistait en 9 sessions avec 13 étudiants inscrits au Département d'anglais. Le processus a commencé par un pré-test et un questionnaire de pré-intervention sur l'auto-efficacité, suivis de sept sessions d'intervention impliquant une interaction avec Pi, durant lesquelles les comportements des étudiants ont été observés à travers une observation semi-structurée. L'expérience s'est terminée par un post-test et un questionnaire de post-intervention, ainsi que par des commentaires réflexifs des participants. Les résultats des entretiens avec les enseignants ont montré une attitude positive envers l'intégration de l'IA en classe. De plus, les résultats ont révélé que Pi avait une influence positive sur la fluidité de la parole et l'auto-efficacité des étudiants. Les scores des post-tests et les réponses aux questionnaires d'auto-efficacité ont significativement augmenté après l'utilisation de Pi, indiquant un effet profond sur les compétences orales.